Pandangan Ulama Mazhab Syāfi’ī tentang Kafālah: Studi Fatwa DSN MUI No.11/DSN-MUI/IV/2000 Tentang Kafālah - Fauzan Agung Pratama; Indra Rustam; Fachri Rinaldy (Jurnal Global Futuristik, 2026)
This study examines the concept of kafālah according to the scholars of the Shāfi‘ī school of thought (madhhab) and contrasts it with the practice of kafālah stipulated in the National Sharia Board-Indonesian Ulema Council (DSN-MUI) Fatwa No. 11/DSN-MUI/IV/2000. Within the Shāfi‘ī school, kafālah is classified as a tabarru‘ (gratuitous) contract, which strictly prohibits the imposition of a fee (ujrah), as asserted by classical scholars such as Al-Māwardī, An-Nawawī, and Ar-Rāfi‘ī. Conversely, the DSN-MUI permits the collection of ujrah in kafālah contracts by employing a contemporary ijtihad approach, utilizing methods such as i‘ādatu an-naẓar. This library research relies on secondary sources, primarily classical texts of the Shāfi‘ī school. The findings reveal a fundamental divergence in legal approaches: the Shāfi‘ī school maintains a rigid adherence to the tabarru‘ principle, whereas the DSN-MUI fatwa seeks to provide practical solutions aligned with the dynamics of the modern Islamic financial industry. This research is expected to offer a scholarly contribution to the development of Islamic economic law in Indonesia.